Breastfeeding in mothers with systemic lupus erythematosus. (August 2016) - Noviani, M; Wasserman, S; Clowse, M E B
Introduction: Breastfeeding is known to improve the well-being of a mother and her infant, and about half of all new mothers breastfeed, but it is unknown how breastfeeding is pursued in systemic lupus erythematosus (SLE; lupus) patients. We sought to determine the rate of breastfeeding and the factors influencing this among women with lupus. In addition, we reassessed the current safety data in lactation of lupus medications. Methods: Data were collected from lupus patients enrolled in a prospective registry who fulfilled the 2012 SLICC criteria, had a live birth, and for whom postpartum breastfeeding status was known. Data included physician assessments of lupus activity and medications, breastfeeding intentions during pregnancy and practice following pregnancy. The safety of medications in breastfed infants was assessed through a comprehensive review of LactMed, a national database about medications in lactation. Results: A total of 51 pregnancies in 84 women with lupus were included in the study. Half of the lupus patients ( n  = 25, 49%) chose to breastfeed. The rate of breastfeeding was not significantly affected by socioeconomic factors. In contrast, low postpartum lupus activity, term delivery, and a plan to breastfeed early in pregnancy were significantly associated with breastfeeding in lupus patients. In reviewing the most up-to-date data, the majority of lupus medications appear to have very minimal transfer into breast milk and are likely compatible with breastfeeding. Conclusion: Half of women with lupus breastfed and most desire to breastfeed. Hydroxychloroquine, azathioprine, methotrexate, and prednisone have very limited transfer into breast milk and may be continued while breastfeeding.